Persistence of plasmid and tet(X4) in an Escherichia coli isolate coharboring blaNDM-5 and mcr-1 after acquiring an IncFII tet(X4)-positive plasmid - Xiao, Xia; Liu, Ziyi; Chen, Xiaojun; Peng, Kai; Li, Ruichao; Liu, Yuan; Wang, Zhiqiang (Frontiers in Microbiology, 2022)
The prevalence of plasmid-mediated tigecycline resistance gene tet(X4) is presenting an increasing trend. Once tet(X4)-bearing plasmids are captured by multidrug-resistant bacteria, such as blaNDM and mcr- coharboring bacteria, it will promote bacteria to develop an ultra-broad resistance spectrum, limiting clinical treatment options. However, little is known about the destiny of such bacteria or how they will evolve in the future. Herein, we constructed a multidrug-resistant bacteria coharboring tet(X4), blaNDM-5, and mcr-1 by introducing a tet(X4)-bearing plasmid into a blaNDM-5 and mcr-1 positive E. coli. Subsequently, we specifically investigated the stability of tet(X4) and the plasmid after evolving under tigecycline or antibiotic-free circumstance, and explored its underlying molecular mechanism. Interestingly, we observed both tet(X4)-bearing plasmids in tigecycline treated strains and non-tigecycline treated strains were stable, which might be jointly affected by the increasing conjugation frequency and the structural alterations of the tet(X4)-positive plasmid. However, the stability of tet(X4) gene showed different scenarios in the two types of evolved strains. The tet(X4) gene in non-tigecycline treated strains was stable whereas the tet(X4) gene was discarded rapidly in tigecycline treated strains. Accordingly, we found the expression levels of tet(X4) gene in tigecycline-treated strains were several times higher than in non-tigecycline treated strains and ancestral strains, which might in turn imposed a stronger burden on the host bacteria. SNPs analysis revealed that a myriad of mutations occurred in genes involving in conjugation transfer, and the missense mutation of marR gene in chromosome of tigecycline treated strains might account for the completely different stability of tet(X4)-bearing plasmid and tet(X4) gene. Collectively, these findings shed a light on the possibility of the emergence of multidrug resistant bacteria due to the transmission of tet(X4)-bearing plasmid, and highlighted that the antibiotic residues may be critical to the development of such bacteria.